PROTEIN-PROTEIN INTERACTION ANALYSIS TO IDENTIFY NUCLEAR FACTOR-ERYTHROID-2 FACTOR 2 (NRF2) INHIBITION BY EXTRACELLULAR ENZYMES FROM WATER KEFIR ORGANISMS - ALIGITA, WIDHYA; SINGGIH, MARLIA; SUTRISNO, ENTRIS; ADNYANA, I. KETUT (International Journal of Applied Pharmaceutics, 2023)
Objective: The study aimed to investigate the interactions between twelve extracellular enzymes and nuclear factor erythroid 2–related factor 2 (Nrf2) in the active site. Methods: The Zdock web server was accessed to perform molecular docking simulations for predicting interactions between the extracellular enzymes and the active site of Nrf2. The Z score analysis revealed enzymes with high scores, indicating strong and statistically significant interactions with Nrf2. Results: DNase 1, a-amylase, and lecithinase C exhibited notably high Z scores, suggesting potential key players in modulating Nrf2-mediated signaling pathways. The examination of salt bridges showed enzymes with more ionic interactions, suggesting enhanced stability and potential for strong binding within the active site of Nrf2. This characteristic might be crucial for enzymatic inhibition of Nrf2’s activity. Conclusion: In conclusion, the findings highlight enzymes, including DNase 1, a-amylase, and lecithinase C, as promising candidates for further exploration as potential inhibitors of NRF2-mediated cellular responses.